2015
DOI: 10.1088/1468-6996/16/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Novel PEPA-functionalized graphene oxide for fire safety enhancement of polypropylene

Abstract: Polypropylene (PP) is a general-purpose plastic, but some applications are constrained by its high flammability. Thus, flame retardant PP is urgently demanded. In this article, intumescent flame retardant PP (IFRPP) composites with enhanced fire safety were prepared using 1-oxo-4-hydroxymethyl-2,6,7-trioxa-1-phosphabicyclo [2.2.2] octane (PEPA) functionalized graphene oxide (PGO) as synergist. The PGO was prepared through a mild chemical reaction by the covalent attachment of a caged-structure organic compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
0
10
0
1
Order By: Relevance
“…They are formed from substances that can be covalently bonded to graphene, such as hexachlorocyclotriphosphazene (HCCP) [75], phenyl dichlorophosphate (PDCP) [76], hyperbranched cyclotriphosphazene polymer [77,78], organophosphorus oligomer [79], N-aminoethyl piperazine [80], silicon-phosphorus oligomer [81], phenyl-bis-(triethoxysilylpropyl) phosphamide [82], ionic liquidcontaining phosphonium [83] and 1-oxo-4-hydroxymethyl-2,6,7-trioxa-1-phosphabicyclo [2,2,2] octane (PEPA) [84]. Bao et al [75] made use of in situ polymerization to functionalize GO with HCCP which acts as a char-catalysing agent (Fig.…”
Section: Molecules-modified Graphene Composite Flame Retardantsmentioning
confidence: 99%
“…They are formed from substances that can be covalently bonded to graphene, such as hexachlorocyclotriphosphazene (HCCP) [75], phenyl dichlorophosphate (PDCP) [76], hyperbranched cyclotriphosphazene polymer [77,78], organophosphorus oligomer [79], N-aminoethyl piperazine [80], silicon-phosphorus oligomer [81], phenyl-bis-(triethoxysilylpropyl) phosphamide [82], ionic liquidcontaining phosphonium [83] and 1-oxo-4-hydroxymethyl-2,6,7-trioxa-1-phosphabicyclo [2,2,2] octane (PEPA) [84]. Bao et al [75] made use of in situ polymerization to functionalize GO with HCCP which acts as a char-catalysing agent (Fig.…”
Section: Molecules-modified Graphene Composite Flame Retardantsmentioning
confidence: 99%
“…retardant property of polymer composites has become a critical issue in industrial application 178. Due to its endothermic and stable layered structure, graphene could act as physical barriers to reduce the diffusion of gases and degradation products, thus prevent the supply of oxygen and play a role of flame retardant 179,. 180 Many works have been reported that graphene can improve the flame retardant properties of PA6 73, 180 and other polymers such as PS 181 , PP 179 , epoxy 182 etc.…”
mentioning
confidence: 99%
“…Kecanduan juga dapat disebabkan oleh perilaku cyberloafing. Cyberloafing adalah perilaku seseorang dalam mengakses internet yang tidak berhubungan dengan pekerjaan yang sedang dikerjakannya (Askew, 2013). Perilaku cyberloafing tidak hanya terjadi di tempat kerja.…”
Section: Pendahuluanunclassified